Smart leadership as an entry point to achieving competitive advantage in the Al-Kharj Governorate Education Department - Al-Masoud, Munirah Abdullah; Darwish, Zainab Awwad Mofleh (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the reality of applying the dimensions of smart leadership (common vision and goals, participatory leadership, leadership of work teams, organizational culture), And to reveal whether there are statistically significant differences in the responses of the sample members to the role of smart leadership in achieving the competitive advantage due to the variables of the study (the number of years of experience, and the educational qualification). To achieve the objectives of the study, the researcher used the descriptive survey method, and adopted the questionnaire as a data collection tool. The study reached a number of results, including: The arithmetic averages of the degrees of agreement of the respondents about the “availability of smart leadership dimensions in the Education Department of Al-Kharj Governorate” came with an arithmetic mean of (4.03) and a high degree of approval, as the dimension of vision and common goals came in the first place with an arithmetic mean of its value. (4.22), and in the last place is the organizational culture dimension with an arithmetic mean of (3.93), and that the arithmetic means of the degrees of agreement of the sample members about the availability of the requirements of “achieving competitive advantage in the Al-Kharj Governorate Education Department” came with an arithmetic mean of (4.01) and a high degree of approval, as it came In the first place was the availability of “physical requirements to achieve competitive advantage” with an arithmetic mean of (4.16), and in the last place came the availability of “technological requirements to achieve competitive advantage” with an arithmetic mean of (3.89). Smart driving in achieving the competitive advantage of the Al-Kharj Governorate Education Department" came with an arithmetic mean of (4.12) and a high degree of agreement. For the two variables (number of years of experience or educational qualification).
Keywords: smart leadership; competitive advantage; Al-Kharj Governorate Education Department